Gangguan Skizofrenia Pada Remaja di Indonesia - Andreas Danang Saputra; Devina Saraswati; Meisye Eka Saputri; Nara Indriani; Liss Dyah Dewi Arini (Institut Nalanda, 2024)
During adolescence, many biological, psychological and social changes occur, but in general the process of physical maturation occurs faster than psychological maturation. During adolescence, there are many things that cause people in general to experience mental disorders. Some mental disorders that usually occur are caused by various existing stressors which can cause anxiety disorders, depression and lead to suicide. Adolescents who grow up in a conducive environment will rarely experience mental disorders which are usually suffered by most teenagers who experience these mental disorders. This mental disorder can be prevented. There are many mental disorders whose symptoms and causes are difficult to determine. It is sometimes difficult to see the difference between ordinary teenage moodiness and signs of more serious illness, although the illness usually begins in late adolescence or young adulthood. Symptoms in adolescents may appear gradually over days, weeks, or weeks. several months or more